2020
DOI: 10.3390/su12198120
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Air Cargo Network on the Regional Economy under the Impact of High-Speed Rail in China

Abstract: There is little research on the impact of air cargo networks on regional economic development, which is especially notable considering that Chinese airlines gradually adjusted their networks after the introduction of high-speed rail (HSR). This empirical study aims to fill this research gap. Firstly, we used the Ordinary Least Squares (OLS) method to study the effect of the air cargo network on the regional economy. The results show that, in eastern and central China, the higher the clustering coefficient of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Different transportation infrastructures have different investment attributes and economic consequences. Most studies have shown that railway and airport infrastructure play a stronger role in driving regional economic integration through its higher transportation efficiency and more complete network system [31,32]. As the basis for connectivity and accessibility of transportation network and the field with the largest number of PPP projects, road infrastructure has significant economic growth effect and positive spatial spillover effect [33], while its spatial spillover effect is weaker than that of railways [34].…”
Section: Heterogeneity Of Transportation Ppp Investment In Different ...mentioning
confidence: 99%
“…Different transportation infrastructures have different investment attributes and economic consequences. Most studies have shown that railway and airport infrastructure play a stronger role in driving regional economic integration through its higher transportation efficiency and more complete network system [31,32]. As the basis for connectivity and accessibility of transportation network and the field with the largest number of PPP projects, road infrastructure has significant economic growth effect and positive spatial spillover effect [33], while its spatial spillover effect is weaker than that of railways [34].…”
Section: Heterogeneity Of Transportation Ppp Investment In Different ...mentioning
confidence: 99%
“…Furthermore, literature has established that, like other economic sectors, the cargo industry is also a key facilitator of economic growth. For example, Hao et al (2020) found that air cargo networks significantly promote GDP per capita in Eastern China. Also, Button and Yuan (2013) found that air freight transport positively impacts local economic development in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided mixed results on the impact of HSR on the local economy. Some studies have shown that the opening of the HSR can promote the process of economic integration, spread the resources of the central city to the surrounding cities, and promote the economic growth of the surrounding cities [11]. Ahlfeldt and Feddersen found that the construction of the HSR greatly optimized the original transportation network, reduced the space and time distances, and had a positive impact on regional economic growth.…”
Section: Introductionmentioning
confidence: 99%